Impact of Immune-Modulatory Drugs on Regulatory T Cell. Issue 11 (November 2016) - Furukawa, Akiko; Wisel, Steven A.; Tang, Qizhi
Abstract : Abstract: Immunosuppression strategies that selectively inhibit effector T cells while preserving and even enhancing CD4 + FOXP3 + regulatory T cells (Treg) permit immune self-regulation and may allow minimization of immunosuppression and associated toxicities. Many immunosuppressive drugs were developed before the identity and function of Treg were appreciated. A good understanding of the interactions between Treg and immunosuppressive agents will be valuable to the effective design of more tolerable immunosuppression regimens. This review will discuss preclinical and clinical evidence regarding the influence of current and emerging immunosuppressive drugs on Treg homeostasis, stability, and function as a guideline for the selection and development of Treg-friendly immunosuppressive regimens. Abstract : Immunosuppressive medications inhibit not only Teff but also Treg. Nevertheless, Treg have different critical intracellular pathways that may allow targeting Teff and not Treg. Several of these differences are not absolute but quantitative. Future Treg friendly treatments will consider which drugs to be used and also what dose to apply.